2017
DOI: 10.1371/journal.pone.0175573
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolomic profiling of eastern honey bee (Apis cerana) infested with the mite Varroa destructor

Abstract: The mite Varroa destructor is currently the greatest threat to apiculture as it is causing a global decrease in honey bee colonies. However, it rarely causes serious damage to its native hosts, the eastern honey bees Apis cerana. To better understand the mechanism of resistance of A. cerana against the V. destructor mite, we profiled the metabolic changes that occur in the honey bee brain during V. destructor infestation. Brain samples were collected from infested and control honey bees and then measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The parameters for LC-MS analysis were set with reference to literature, with some modifications 41 . The samples were subjected to a 2777 C UPLC (Waters, UK) coupled with an Xevo G2 XS QTOF high-resolution tandem mass spectrometer (Waters, UK).…”
Section: Metabolite Extraction and Analysis For Lc-msmentioning
confidence: 99%
“…The parameters for LC-MS analysis were set with reference to literature, with some modifications 41 . The samples were subjected to a 2777 C UPLC (Waters, UK) coupled with an Xevo G2 XS QTOF high-resolution tandem mass spectrometer (Waters, UK).…”
Section: Metabolite Extraction and Analysis For Lc-msmentioning
confidence: 99%
“…The study of aqueous metabolites of insects, which may involve whole insects or specific fluids, has been developing through the use of both mass spectrometry and NMR-based methods [4][5][6][7][8][9][10][11][12][13][14]. Studies may include a focus on specific organs such as the brain [4,5,10,15], which is particularly of interest because metabolic dysregulation has been attributed to this organ, particularly owing to neonicotinoids and pesticides [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity considerations have emphasized the need for either mass spectrometry approaches [4,5] or specialized hardware [12]. To improve sensitivity as well as to measure average properties, pooling of multiple bees in samples is also an option [8][9][10][11]14,25]. The work reported here builds on a recent result in detecting proline in the honeybee brain by NMR [15] to further develop the feasibility of single bee and single bee brain NMR of aqueous metabolites on relatively conventional NMR instrumentation, employing high field (14.1 T) and low field (1.88 T) NMR instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Although hymenoptaecin showed the greatest increase in expression, its expression level was more consistent in between two time-points (Cornman et al, 2013). Wu et al (2017) suggested that it is important to understand the synergistic effects of parasitism on honeybee colonies. Understanding the resistance mechanisms of the honeybees against pathogens and parasites will help in breeding hybrids, pathogen-and parasite-resistant bees and the development of rationally designed pathogen and parasite prevention methods.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics, a comprehensive quantitative and qualitative analysis of all metabolites in samples, can be used to evaluate the metabolic processes under given physiological and pathological conditions (Nicholson and Lindon, 2008). Wu et al (2017) studied the metabolomic profile of brains of healthy and V. destructor infested A. cerana using untargeted LC-MS/MS. After multivariate statistical analyses, 64 days regulated metabolites, including fatty acids, amino acids, carboxylic acid and phospholipids were identified.…”
Section: Introductionmentioning
confidence: 99%